Pengaruh Empowering Leadership dan Inter Organizational Knowledge Sharing Terhadap Kinerja Karyawan Dengan Kecerdasan Digital Sebagai Variabel Moderasi - Novi Nuryani; Dita Prameswari (LPPM Universitas An Nuur, 2024)
Background: The rapid development of science and technology has brought changes to human resources in organizations. These changes result in every employee being required to improve their performance. Increasing employee performance can be done through empowering leadership and inter-organizational knowledge sharing which is supported by digital intelligence.Purpose: The aim of this research is to find out how empowering leadership and interorganizational knowledge sharing influence employee performance with digital intelligence as a moderating variable.Methods: This research uses an explanatory quantitative approach which aims to test the formulated hypothesis. Determining the number of samples using the Slovin formula with certain criteria and obtaining a sample of 100. The method used is Partial Least Square (PLS).Results: The research results show that empowering leadership and inter-organizational knowledge sharing have a positive and significant influence on employee performance, digital intelligence does not moderate the relationship between empowering leadership and employee performance. And digital intelligence is able to moderate the relationship between inter-organizational knowledge sharing and employee performance.Conclusion: Empowering leadership and inter-organizational knowledge sharing play a role in improving employee performance. Digital intelligence does not moderate the relationship between empowering leadership and employee performance. And digital intelligence moderates the relationship between inter-organizational knowledge sharing and employee performance.Suggestion: It is recommended for researchers who want to conduct research on the same issue to add other variables, for example bleisure.